2018
DOI: 10.1055/s-0038-1661386
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and Malignancy: The Clinical Performance of Non–Vitamin K Oral Anticoagulants—A Systematic Review

Abstract: Atrial fibrillation (AF) is commonly diagnosed in the setting of active cancer. Because of an increased risk of either thromboembolic events or bleeding, the decision to initiate therapeutic anticoagulation in patients with active cancer can be challenging. Moreover, little is still known about the optimal anticoagulation therapy in the setting of AF and cancer, and no guidelines are as yet available. Considering that nonvitamin K antagonist oral anticoagulants (NOACs) are recommended as alternatives to vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 21 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…NOACs are safe and effective alternatives to VKA therapy [46,47,48,49], and are currently considered as first-line therapy for long-term stroke prevention in patients with nonvalvular AF [6]. The overall safety and efficacy profile of NOACs have been confirmed in different clinical scenarios [50,51,52,53,54,55,56,57,58]. The clinical performance of NOACs in the setting of acute and elective CV has been addressed by three prospective randomized trials.…”
Section: Prevention and Treatment Of Left Atrial Appendage Thrombosismentioning
confidence: 99%
“…NOACs are safe and effective alternatives to VKA therapy [46,47,48,49], and are currently considered as first-line therapy for long-term stroke prevention in patients with nonvalvular AF [6]. The overall safety and efficacy profile of NOACs have been confirmed in different clinical scenarios [50,51,52,53,54,55,56,57,58]. The clinical performance of NOACs in the setting of acute and elective CV has been addressed by three prospective randomized trials.…”
Section: Prevention and Treatment Of Left Atrial Appendage Thrombosismentioning
confidence: 99%
“…The evaluation of apixaban serum level at peak and trough time demonstrated the therapeutic drug levels in our morbid obese patient and the stability of apixaban plasma levels even when the patient has lost weight. The use of plasma level monitoring for NOAC doseadjustment is discouraged for the vast majority of patients due to the lack of outcome data to support such an approach; however, in rare cases of potentially substantial drug-drug interactions; 23,24 in special population in which the use of NOACs is still debated, 25,26 or in case of not deferrable cardiac or non-cardiac interventional or surgical procedures, 27 a "patient-centered approach", including the plasmatic drug evaluation, might be considered for choosing the more appropriate anticoagulant molecule.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, the induction of the anticoagulant effect is eased without having to resort to the administration of heparin [28,29]. Moreover, both the safety and efficacy of NOACs have been positively tested in a randomized clinical trial [30] and confirmed by several clinical real-world casuistries [1,31,32,33,34,35].…”
Section: Novel Oral Anticoagulants (Noacs): a Future Already Presentmentioning
confidence: 99%